Surrealism, Occultism and Politics: In Search of the Marvellous - Bauduin, Tessel M.; Ferentinou, Victoria ca. 20. Jh.; Zamani, Daniel (Studies in Surrealism, 2018)
Machine generated contents note: pt. I Alternative Modes of Knowledge -- 1.Spiritual Surrealists: Seances, Automatism, and the Creative Unconscious / Claudie Massicotte -- 2.The Vertiginous Pursuit of the Grand Jeu: Experimental Metaphysics, Paramnesia, and Creative Involution / Donna Roberts -- 3.Palmistry as Portraiture: Dr. Charlotte Wolff and the Surrealists / M. E. Warlick -- 4.Occulted Un-Knowing: Bataillean Approaches to the Sacred in Gellu Naum's Ceasornicaria Taus and Alejo Carpentier's El Siglo de las Luces / Vivienne Brough-Evans -- pt. II Myth, Magic and the Search for Re-Enchantment -- 5.Melusina Triumphant: Matriarchy and the Politics of Anti-Fascist Mythmaking in Andre Breton's Arcane 17 (1945) / Daniel Zamani -- 6.Esotericism and Surrealist Cinema: Wilhelm Freddie's Films and the New Myth / Kristoffer Noheden -- 7.Disenchanted Ground, or Antonin Artaud, Vincent van Gogh and Magic in 1947 / Gavin Parkinson